Civil Society: Relevansinya dengan Kenyataan Sosial Umat Islam Indonesia (Studi Pemikiran Tafsir Nurcholish Madjid) - Farida Nur Afifah (IAIN Bengkulu, 2020)
Nurcholish Madjid is a Muslim scholar who is in direct contact with the Eastern world and the Western world and Nurcholish Madjid's thought in interpreting the Qur'an and Islam. In addition, there were three causes that influenced his first thought, the figure who would not be trapped in a traditionalist-modernist dichotomy. Secondly, it is a figure that has systematically formulated a comprehensive basic view of the Islamic. The three figures are actively involved in the socio-political field. Therefore, he was said to be the successor of the Islamic neo-modernist thought especially the successor of Fazlur Rahman. The pattern of interpretation is the interpretation of Maudhu'i with the attention of al-muhafazah ‘ala al-qadim al-salih wa al-akhdh bi’l-jadid al-aslah. This paper will present the view of the Nurcholish Madjid regarding civil society and will be explored using the literature method. As for the results of this search are In interpreting the civil society Nurcholish Madjid equates with civil society that is a civilisation society that exempts the example of Prophet Muhammad in shaping and cultivating the community in Medina. People who obey the law, appreciate the difference of opinion and the rights of others, and have a concern for the sense of humanity. It can be said that Indonesian people need hard efforts in establishing civil society as conceptualized by Nurcholish Madjid.